Juvenile pubic symphysiodesis: Case report in a canine (Revista Sistemas de Producción Agroecológicos, 2025)
Passive laxity of the hip joint and underlying subluxation are the main risk factors for the development of osteoarthritis, which are the primary signs of hip dysplasia in dogs. Therefore, early diagnosis and surgical treatment should be performed to prevent future joint disease. By diagnosing coxofemoral laxity early in puppies less than 20 weeks of age, preventive/therapeutic measures can be taken to reduce the prevalence of the disease. This case report describes the diagnosis and treatment of a 12-week-old male Siberian husky that was brought to the Veterinary Clinical Center at the University of Los Llanos with clinical signs of lameness in the right hind limb. The orthopedic examination revealed passive laxity of the hip joint and tarsal joint of both limbs. A radiographic study of the hip and tarsal joints was performed, revealing bilateral laxity and joint incongruity of the hip and bilateral joint laxity in the proximal and distal intertarsal joints. Juvenile pubic symphysiodesis was performed as surgical treatment. Juvenile pubic symphysiodesis is a less invasive technique compared to other pelvic osteotomies and has a less complex postoperative period. Although it requires early diagnosis, it has been shown to slow the progression of dysplasia, reduce pain, and decrease medication use over long periods.